Pengembangan Aplikasi Pengatur Kalori Harian menggunakan Tensorflow berbasis Android - Naufal Afif Bunyamin; Adam Hendra Brata; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Regulation of calories that enter the body is one way to achieve a healthy lifestyle. Therefore, daily calorie regulation is very important to maintain health and lead a healthy life. However, based on the results of the Riset Kesehatan Dasar (Riskesdas) in 2018 it shows that the nutritional status of Indonesian people still does not meet the standards. To avoid diseases that arise due to unbalanced nutrition, it is necessary to adjust a good and correct diet. Automatic calorie regulaton can be implemented in smartphones that make it easier for individuals both in term of practicality and mobility. In this study, the development of a daily calorie control application, namely Foodivore, is an android-based application that can help regulate the amount of daily calorie consumption. Foodivore has several features such as scanning food, managing consumption plans, and getting information about health. Foodivore uses Tensorflow technology which allows applications to identify an object based on an artificial intelligence model. The method used in the development of the Foodivore system is Kanban Agile due to changing needs and speed in delivering applications. The usability test results have a value of 85 which categorizes the application as an application with a good level of use. In addition, unit testing and User Acceptance Test (UAT) tests show a 100% success rate of each test which concludes that the application is running well.